An ontology driven question answering system for fatawa retrieval - Benlaharche Keltoum; Zakaria Laboudi; Nabila Nouaouria; Djamel Eddine Zegour (Institute of Advanced Engineering and Science, 2021)
This work aims to propose a system for the Algerian Fatawa House in orderto facilitate the task of the Expert Mufti who is responsible of giving fatawa for Algerian people inquiries. In fact, as this house is recent and does not have sufficient human resources, it is difficult to satisfy all inquiries coming daily, this leads the askers to wait for a long time before getting answers. The proposed system allows the askers to express concerns they may have. By using a case-based reasoning mechanism combined with ontology domain, the system tries to retrieve similar cases from the knowledge base. In the casewhere the response already exists, the system immediately provides the answer to the askers. Otherwise, an inquery is automatically formulated and sent to the expert Mufti-which is a certified scholar-in order either to validate the generated response by the system or give a new answer. Such a question-answering system may be very helpful for askers to get their answers faster since it allows both the storage of previous fatawas and their retrieval for processing coming inquiries. To validate our proposal, we rely on fatawas concerning the Islamic finance and banking transactions domain. Overall, the results are encouraging and satisfactory.